Designing development for rice agricultural community in Delanggu Subdistrict, Klaten Regency, Indonesia: enhancements based on regional cultural and natural potentials studies / Pandu Purwandaru ... [et al.] - Purwandaru, Pandu; Utami, Lira Anindita; Ardianto, Deny; Mataram, Sayid (Universiti Teknologi MARA, Perak, 2022)
Delanggu district area has many rice-cultural potentials that can be developed. Having emerged from a traditional farming culture, some of these agricultural potentials include farming rituals, festivals, and planting methods, as well as the local rice variety of Rojolele Delanggu. Although traditionally present in the everyday life of the community, they are yet to be considered as real regional potentials. Consequently, they have not been utilized as significant elements for community building. Thus, with designers involved as facilitators, several projects have been carried out in collaboration with the farming community to re-recognize and encourage the revival of this particular living culture centered around traditional farming activity. The main activities include (1) mapping of treasure-and-stakeholders, (2) formulating ideas and making project priority scales, and (3) implementation of local-guest participatory activities. In this project, the main activities relate to re-introducing traditional agriculture, replanting Rojolele rice, and developing straw crafts.